Vitamin E Attenuates the Progression of Non-Alcoholic Fatty Liver Disease Caused by Partial Hepatectomy in Mice. - Golnar Karimian (PLoS ONE, 2015)
The progression of non-alcoholic fatty liver disease (NAFLD) likely involves a 'multiple hit' mechanism. We hypothesized that partial hepatectomy, a procedure performed frequently in patients with NAFLD, would accelerate the progression of disease.C57BL/6JolaHsd mice were fed a choline-deficient L-amino acid-defined diet (CD-AA) or a choline-sufficient L-amino acid-defined control diet (CS-AA). Part of the mice in the CD-AA group received a diet enriched in vitamin E (~20 mg /day). Two weeks after the start of the diet, mice underwent a partial hepatectomy or a sham operation.In the CD-AA group, NAFLD activity scores were significantly higher at 7 days after partial hepatectomy compared to the sham operated mice (3.7 ± 1.3 vs. 1.8 ± 0.7; P<0.05). In addition, TBARS, a measure for oxidative stress, in liver tissue of the CD-AA group were significantly higher at day 1, 3 and 7 after partial hepatectomy compared to the sham operated mice (P<0.05). Vitamin E therapy significantly reduced TBARS level at day 7 after partial hepatectomy compared to the CD-AA diet group (P< 0.05). Vitamin E suppletion reduced NAFLD activity score at day 7 after partial hepatectomy compared to the CD-AA group (2.3 ± 0.8 vs. 3.8 ± 1.0; P<0.05).Partial hepatectomy accelerates the progression of NAFLD. Disease progression induced by partial hepatectomy is substantially attenuated by vitamin E.